Characteristics of denitrification and microbial community in respect to various H2 pressures and distances to the gas supply end in H2-based MBfR - Li, Haixiang; Sun, Ruize; Zhang, Xuehong; Lin, Hua; Xie, Yi; Han, Yu; Pan, Yongxing; Wang, Dunqiu; Dong, Kun (Frontiers in Microbiology, 2022)
The hydrogen-based hollow fiber membrane biofilm reactor (H2-based MBfR) has shown to be a promising technology for nitrate reduction. Hollow fiber membranes (HFM) operating in a closed mode in an H2-based MBfR often suffer from reverse gas diffusion, taking up space for the effective gas substrate and resulting in a reduction in the HFM diffusion efficiency, which in turn affects denitrification performance. Because the H2 supply pressure is considered the key to influencing the denitrification performance, in this work, we developed a laboratory-scale H2-based MBfR, which operated in a closed mode to investigate the dynamics of denitrification performance and biofilm microbial community analysis at different H2 supply pressures. A faster formation of biofilm on the HFM and a shorter start-up period were found for a higher H2 supply pressure. An increase in the H2 pressure under 0.08 MPa could significantly promote denitrification, while a minor increase in denitrification was observed once the H2 pressure was over 0.08 MPa. Sequencing analysis of the biofilm concluded that i) the dominant phylum-level bacteria in the reactor during the regulated hydrogen pressure phase were Gammaproteobacteria and Alphaproteobacteria; ii) when the hydrogen pressure was 0.04–0.06 MPa, the dominant bacteria in the MBfR were mainly enriched on the hollow fiber membrane near the upper location (Gas inlet). With a gradual increase in the hydrogen pressure, the enrichment area of the dominant bacteria in MBfR gradually changed from the upper location to the distal end of the inlet. When the hydrogen pressure was 0.10 MPa, the dominant bacteria were mainly enriched on the hollow fiber membrane in the down location of the MBfR.